ANALISIS PERMINTAAN IMPOR BAWANG MERAH DI INDONESIA - Theresia Wediana Pasaribu; Murni Daulay (Ekonomi dan Keuangan, 2013)
This research has a purpose to know the development of import demand of shallot in Indonesia and what influence national consumption of shallot, national income, production of shallot, price of import shallot, exchange rate and volume of shallot import have of import demand of shallot in Indonesia. This research uses time series data from 2002 to 2012 by using linier equation. Analysis method that is used in this research is multiple regression by using Ordinary Least Square (OLS) method. The regression result shows that National Consumption of shallot has positive influence but does not significantly influence import demand of shallot while income has positive influence and significantlyinfluence import demand of shallot. Price of import shallot has positive influence and significantly influence import demand of shallot while the increasing of shallot’s price does not decrease the amount of import demand of shallot because other factors beside price have bigger influence of import demand of shallot. National production has negative influence and significantly influence import demand of shallot while exchange rate and the volume of shallot import one year prior to current year have negative influence but do not significantly influence import demand of shallot.Keyword : import, demand, shallot